1997
DOI: 10.1021/es970215h
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Sexual Differentiation in Genetic Male Common Carp (Cyprinus carpio) Exposed to an Alkylphenol during Different Life Stages

Abstract: A genetically male population of the common carp, Cyprinus carpio, was exposed to a measured concentration of 0.14 mg/L 4-tert-pentylphenol (TPP) for various periods before and during sexual differentiation in order to determine the presence of a labile period for endocrine disruption. Exposure to TPP for 3 days during the embryo-larval period did not affect the process of sexual differentiation nor the proliferation of the primordial germ cells. Longer exposures, starting before and including sexual different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 55 publications
4
76
1
1
Order By: Relevance
“…In male fish, elevated vtg may indicate exposure to xenoestrogens. Concentrations in two male carp from Station 511 were within the range of early-to mid-vitellogenic females (Table 6), a condition that has been associated with the exposure of male fish to exogenous estrogens in both field and laboratory studies (e.g., Folmar et al, 1996Folmar et al, , 2001Gimeno et al, 1997;Jobling et al, 1998). In addition, and keeping with the findings of most field studies (e.g., Goodbred et al, 1997;Lee et al, 2000;McDonald et al, 2002;Solé et al, 2002Solé et al, , 2003, none of the vitellogenic male carp were intersex.…”
Section: Reproductive Biomarkerssupporting
confidence: 68%
“…In male fish, elevated vtg may indicate exposure to xenoestrogens. Concentrations in two male carp from Station 511 were within the range of early-to mid-vitellogenic females (Table 6), a condition that has been associated with the exposure of male fish to exogenous estrogens in both field and laboratory studies (e.g., Folmar et al, 1996Folmar et al, , 2001Gimeno et al, 1997;Jobling et al, 1998). In addition, and keeping with the findings of most field studies (e.g., Goodbred et al, 1997;Lee et al, 2000;McDonald et al, 2002;Solé et al, 2002Solé et al, , 2003, none of the vitellogenic male carp were intersex.…”
Section: Reproductive Biomarkerssupporting
confidence: 68%
“…GSI is used as a biomarker for exposure of aquatic wildlife to environmental estrogens, since a correlation has been established in male fish between the inhibition of testicular growth and the potency of estrogenic compounds [4,9,22]. Field studies have reported that estrogenic chemicals decrease the GSI of exposed fish [1,14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Three-month exposure to a sublethal dose of 4-tert-pentylphenol or 17β-estradiol causes progressive disappearance of spermatozoa and spermatogenic cysts, and reduces the seminiferous tubule diameter, in mature male carp [11]. Ovo-testes were found in juvenile carp exposed to xeno-estrogens during sexual differentiation [8,9]. However, a field study on adult crucian carp (Carassius carassius) living in a pond containing treated pulp mill effluent showed no gonadal deformation or feminization of male gonads [23].…”
mentioning
confidence: 99%
“…These endocrine disruptors may cause a variety of problems with growth, development, reproduction, and behavior (Kavlock et al 1996). Gonadal abnormality and reproductive impairment caused by endocrine disruptors have been documented in fish (Edmunds et al 2000;Gimeno et al 1997;Gray and Metcalfe 1997), turtles (Guillette et al 1994(Guillette et al , 1996Willingham and Crews 1999), minks (Harding et al 1999;Heaton et al 1995), and birds (Fry et al 1987;Halldin et al 1999). However, information about gonadal differentiation in amphibians involving endocrine disruptors is relatively scarce.…”
mentioning
confidence: 99%